Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Conflict between Ingushetia and North Ossetia; a joint meeting of the Council of Republics and the Council of Nationalities of the Russian Federation; an oppositional rally near the House of Soviets and a rally by Yeltsin's supporters on Arbat Square in Moscow. Featured in the program: Khasbulatov, Ruslan Imranovich (Chairman of the Supreme Soviet of the Russian Federation); Sokolov, Veniamin (Chairman of the Soviet of the Republic of the Russian Federation) Contributors: Berdnikova, Nina (Anchor) Series description: A program about the activity of the Supreme Soviet of the Russian Federation. Ингушско-осетинский конфликт; совместное заседание Совета Республик и Совета национальностей Российской Федерации; митинг сторонников оппозиции у Дома Советов и митинг сторонников Ельцина на Арбатской площади в Москве. В программе участвуют: Хасбулатов, Руслан Имранович (Председатель Верховного Совета Российской Федерации); Соколов, Вениамин (Председатель Совета Республики Верховного Совета России) Создатели: Бердникова, Нина (Ведущий/Ведущая) Описание серии: Передача о деятельности Верховного Совета Российской Федерации.